2022
DOI: 10.1002/adma.202107964
|View full text |Cite
|
Sign up to set email alerts
|

Transforming the Chemical Structure and Bio‐Nano Activity of Doxorubicin by Ultrasound for Selective Killing of Cancer Cells

Abstract: Reconfiguring the structure and selectivity of existing chemotherapeutics represents an opportunity for developing novel tumor‐selective drugs. Here, as a proof‐of‐concept, the use of high‐frequency sound waves is demonstrated to transform the nonselective anthracycline doxorubicin into a tumor selective drug molecule. The transformed drug self‐aggregates in water to form ≈200 nm nanodrugs without requiring organic solvents, chemical agents, or surfactants. The nanodrugs preferentially interact with lipid raft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…4d is the accumulation of nanomicelles in the lung, liver and spleen in both nanomicelle cases, which is plausibly ascribed to the enrichment of macrophages in these organs in our tumor-bearing model mice. 48,49 It should also be noted that further calculation of the signal ratio of the tumor/lung revealed an appreciable discrepancy in terms of targeting ability. Specifically, the ratio in the IR@MFH group was ∼2.08, while that in the IR@M group was ∼1.14.…”
Section: Papermentioning
confidence: 99%
“…4d is the accumulation of nanomicelles in the lung, liver and spleen in both nanomicelle cases, which is plausibly ascribed to the enrichment of macrophages in these organs in our tumor-bearing model mice. 48,49 It should also be noted that further calculation of the signal ratio of the tumor/lung revealed an appreciable discrepancy in terms of targeting ability. Specifically, the ratio in the IR@MFH group was ∼2.08, while that in the IR@M group was ∼1.14.…”
Section: Papermentioning
confidence: 99%
“…DOX is generally thought to have two main antitumor mechanisms: one is binding with DNA and inhibiting its replication; the other is destroying the mitochondrial respiratory chain and producing ROS. 39 When DOX enters the mitochondria, electrons are obtained from the electron transport chain (ETC), semiquinone intermediates are formed, and then the electrons are transferred to oxygen (O 2 ) through a redox reaction to produce ROS. 11 Therefore, to explore the antitumor mechanism of AD@PLGA−PEG NPs, we first investigated their intracellular accumulation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This result was consistent with the literature report. 39 Therefore, we speculated that if the AD@PLGA−PEG NPs mainly entered the mitochondria and produced ROS, ABZ could help to produce more ROS so the AD@PLGA−PEG NPs could show a good inhibitory effect on tumor cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Based on laboratory scale reactions, it has been found that acoustic cavitation derived from sound waves can promote chemical modification, polymerization and self-assembly of phenolic molecules into nanoparticles without using external chemical agents [14] , [21] , [22] , [23] . Bhangu et al have reported the synthesis of a carrier-free nanodrug made from non-selective anthracycline doxorubicin into a tumour selective drug nanoparticle by using high-frequency ultrasound [24] . It was demonstrated that the oscillating surface of acoustic cavitation bubbles acts as a catalytic binding site, inducing self-assembly of modified molecules at transient gas-liquid interfaces as a result of high local concentration and strong intermolecular interactions upon bubble implosion.…”
Section: Introductionmentioning
confidence: 99%